Large random telegraph noise in sub-threshold operation of nano-scale nMOSFETs - Campbell, J.P.; Yu, L.C.; Cheung, K.P.; Qin, J.; Suehle, J.S.; Oates, A.; Sheng, K. (2009 IEEE International Conference on IC Design and Technology, 2009)
We utilize low-frequency noise measurements to examine the sub-threshold voltage (sub-V TH ) operation of highly scaled devices. We find that the sub-V TH low-frequency noise is dominated by random telegraph noise (RTN). The RTN is exacerbated both by channel dimension scaling and reducing the gate overdrive into the sub-V TH regime. These large RTN fluctuations greatly impact circuit variability and represent a troubling obstacle that must be solved if sub-V TH operation is to become a viable solution for low-power applications.